Calculations of gaseous and particulate emissions from German agriculture 1990 - 2012: Report on methods and data (RMD) Submission 2014; Berechnung von gas- und partikelförmigen Emissionen aus der deutschen Landwirtschaft 1990 - 2012: Report zu Methoden und Daten (RMD) Berichterstattung 2014 - Hans-Dieter Haenel; Claus Rösemann; Ulrich Dämmgen; Eike Poddey; Annette Freibauer; Sebastian Wulf; Brigitte Eurich-Menden; Helmut Döhler; Carsten Schreiner; Beate Bauer; Bernhard Osterburg (Johann Heinrich von Thünen-Institut, 2014)
The report at hand (including a comprehensive annex of data) serves as additional document to the National Inventory Report (NIR) on the German green house gas emissions and the Informative Inventory Report (IIR) on the German emissions of air pollutants (especially ammonia). The report documents the calculation methods used in the German agricultural inventory model GAS-EM as well as input data, emission results and uncertainties of the emission reporting submission 2014 for the years 1990 - 2012. In this context the sector Agriculture comprises the emissions from animal husbandry and the use of agricultural soils. As required by the guidelines, emissions from activities preceding agriculture, from the use of energy and from land use change are reported elsewhere in the national inventories. The calculation methods are based in principle on international guidelines for emission reporting and have been continuingly improved during the past years. This concerns especially the calculation of energy requirements, feeding and the N balance of the most important animal categories. In addition, technical mitigation measures such as air scrubbing and digestion of slurry have been taken into account. [...] – – Der vorliegende Berichtsband einschließlich des umfangreichen Datenanhangs dient als Begleitdokument zum National Inventory Report (NIR) über die deutschen Treibhausgas-Emissionen und zum Informative Inventory Report (IIR), über die deutschen Schadstoffemissionen (insbesondere Ammoniak). Er dokumentiert die im deutschen landwirtschaftlichem Inventarmodell GASEM integrierten Berechnungsverfahren sowie die Eingangsdaten, Emissionsergebnisse und Unsicherheiten der Berichterstattung 2014 für die Jahre 1990 bis 2012. Der Bereich Landwirtschaft umfasst dabei die Emissionen aus der Tierhaltung und der Nutzung landwirtschaftlicher Böden. Emissionen aus dem Vorleistungsbereich, aus der Nutzung von Energie sowie Landnutzungsänderungen werden den Regelwerken entsprechend an anderer Stelle in den nationalen Inventaren berichtet. Die Berechnungsverfahren beruhen in erster Linie auf internationalen Regelwerken zur Emissionsberichterstattung und wurden in den vergangenen Jahren beständig weiterentwickelt. Dies betrifft im Wesentlichen die Berechnung des Energiebedarfs, der Fütterung und der tierischen N-Bilanz bei den wichtigen Tierkategorien. Zusätzlich wurden technische Minderungsmaßnahmen wie Abluftreinigung und Güllevergärung berücksichtigt. [...]
urn:nbn:de:gbv:253-201403-dn053407-5
Keywords: 630